Self‐Templated Conversion of Metallogel into Heterostructured TMP@Carbon Quasiaerogels Boosting Bifunctional Electrocatalysis. (10th July 2019) - Guo, Hele; Feng, Qichun; Xu, Kaiwen; Xu, Jingsan; Zhu, Jixin; Zhang, Chao; Liu, Tianxi
Abstract: Integration of nanostructured electrocatalysts into a 3D ordered assembly is beneficial for boosting their catalytic performance across various energy conversion applications. In this work, a self‐templated carbonization strategy for synthesizing heterostructures of transition metal phosphide@nitrogen/phosphorus dual‐doped carbon quasiaerogels (TMP@NPCA) is presented using a rationally designed precursor of a metallogel with Zn/M (M = Co, Fe, and Ni) bimetallic clusters (BMOG) and nitrogen/phosphorus chelate ligands. During the self‐templated carbonization, the Zn ions among the BMOG boost a simultaneous catalytic carbonization and activation process of the resultant TMP@NPCA, whereas the M ions offer a versatile self‐phosphating preparation of TMP nanoparticles (e.g., CoP, FeP, and Ni2 P) within the TMP@NPCA. As a proof of concept, the TMP@NPCA catalysts deliver an excellent bifunctional catalytic activity and outstanding stability toward the oxygen reduction reaction and hydrogen evolution reaction, offering competitive advantages to achieve supreme bifunctional catalysis performance over the state‐of‐the‐art TMP catalysts for renewable energy conversion systems. Abstract : Heterostructured transition metal phosphide@nitrogen/phosphorus dual‐doped carbon quasiaerogels are prepared via self‐templated carbonization from a metallogel containing Zn/M (M = Co, Fe, and Ni) bimetallic cluster precursor, which can readily work as a highly active and durable oxygen reduction reaction/hydrogen evolution reaction bifunctional electrocatalyst.